KOMPETENSI INDIVIDU, KOMUNIKASI, KECERDASAN EMOSIONAL, DAN BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI KPU PROVINSI MALUKU - Zacharias, Tehubijuluw (Lembaga Penelitian dan Pendidikan Mandala, 2022)
Abstract: This study aims to analyze the influence of individual competence, communication, emotional intelligence and organizational culture on employee performance. The population in this study includes all employees at the Maluku Provincial Election Commission totaling 30 people with saturated sample determination. Analysis using multiple linear regression with the help of SPSS 20.00. The results showed that individual competence, communication, emotional intelligence and organizational culture had a positive and significant effect partially and simultaneously on employee performance at the Maluku Provincial Election Commission, where individual competency variables had the most dominant influence on employee performance at KPU Maluku Province.